Citizens' Assemblies for Referendums and Constitutional Reforms: Is There an “Irish Model” for Deliberative Democracy? - Courant, Dimitri (Frontiers in Political Science, 2021)
Among democratic innovations, deliberative mini-publics, that is panels of randomly selected citizens task to make recommendations about public policies, have been increasingly used. In this regard, Ireland stands out as a truly unique case because, on the one hand, it held four consecutives randomly selected citizens’ assemblies, and on the other hand, some of those processes produced major political outcomes through three successful referendums; no other country shows such as record. This lead many actors to claim that the “Irish model” was replicable in other countries and that it should lead to political “success”. But is this true? Relying on a qualitative empirical case-study, this article analyses different aspects to answer this question: First, the international context in which the Irish deliberative process took place; second, the differences between the various Irish citizens’ assemblies; third, their limitations and issues linked to a contrasted institutionalisation; and finally, what “institutional model” emerges from Ireland and whether it can be transferred elsewhere.